Temporal characterization of biogas slurry: a pre-requisite for sustainable nutrigation in crop production - Yadav, Rashmi; Sudhishri, Susama; Khanna, Manoj; Lal, Khajanchi; Dass, Anchal; Kushwaha, H. L.; Bandyopadhyay, Kalikinkar; Dey, Abir; Kushwah, Ajay; Nag, Ramineni Harsha (Frontiers in Sustainable Food Systems, 2023)
Biogas slurry serves as a useful organic fertilizer due to its substantial nutrient content, and its characterization enables the evaluation of nutrient content and its efficient utilization. This study focuses on the variations in the nutrient content of biogas slurry from different dairy farm systems located near the ICAR-Indian Agricultural Research Institute (IARI) (New Delhi), Daryapur Kalan (New Delhi), and Madanpur (Uttar Pradesh) during the pre-monsoon, monsoon, and post-monsoon seasons. The study reveals significant variations in macronutrient levels, particularly nitrogen (N), which showed variations exceeding 3% and a wider range of almost 6% during the pre-monsoon and post-monsoon periods. Spatial differences between dairy farms also contributed to the variance, with more than 10% differences observed between IARI and Daryapur Kalan and between IARI and Madanpur. Phosphorus (P) remained stable across seasons with spatial variation, while potassium (K) exhibited a reverse trend. Correlation analysis highlighted strong positive associations between N content and phosphorus (0.959), organic carbon (0.954), pH (0.813), and electrical conductivity (0.806). The findings suggest the use of biogas slurry has a potential to reduce the synthetic fertilizer consumption of N, P, and K by approximately 8.78%, 11.01%, and 14.33%, respectively and using them for further for nutrigation.